El impacto del subempleo en la desigualdad socioeconómica en la Parroquia del Centro Histórico de Quito, durante el periodo 2020-2023 - Rodriguez Cumbicos, Steeven Ederson (2025)
This study analyzed the impact of underemployment on socioeconomic inequality in the Historic Center of Quito during the period 2020-2023. A mixed methodology was used, which integrated surveys of people in underemployment situations and the analysis of secondary data from official sources. The aim was to identify how precarious working conditions affect income distribution, access to basic services, and the quality of life of underemployed workers. The results showed that underemployment amplifies socioeconomic inequalities, exacerbating vulnerabilities in the studied population. The study concludes that it is urgent to design public policies focused on promoting labor formalization and equitable access to economic opportunities to reduce inequality gaps in similar areas.